The United States and Asia regional dynamics and twenty-first-century relations - Sutter, Robert G. (Asia in world politics, 2015)
This book offers a cogent overview of U.S. relations with Asia. Noted scholar Sutter provides a balanced analysis of post-Cold War dynamics in Asia. He assesses how the United States has responded to Asia's growing strength while at the same time trying to maintain its leading position as an Asian power despite China's rising influence.